2020
DOI: 10.1248/cpb.c19-00634
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship Study on Col-003, a Protein–Protein Interaction Inhibitor between Collagen and Hsp47

Abstract: This study demonstrates the structure-activity relationship of Col-003, a potent collagen-heat-shock protein 47 (Hsp47) interaction inhibitor. Col-003 analogues were successfully synthesized by Pd(0)-catalyzed cross-coupling reactions of 5-bromosalicylaldehyde derivatives with alkyl-metal species, and the inhibitory activities of the synthetic analogues were evaluated using surface plasmon resonance analysis (BIAcore). We succeeded in discovering two potent inhibitors that showed 85 and 81% inhibition at a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The Col003 compound was synthesized as previously reported (4). The synthesis of Col049, Col050, and Col051 is described in the study (27), where Col049, Col050, and Col051 refers to 5eE, 5eF, and 5eG, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The Col003 compound was synthesized as previously reported (4). The synthesis of Col049, Col050, and Col051 is described in the study (27), where Col049, Col050, and Col051 refers to 5eE, 5eF, and 5eG, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, they synthesized Col003 via Pd(0)-catalyzed cross-coupling reactions of 5-bromosalicylaldehyde derivatives with alkyl metal species. Two potent inhibitors were discovered that inhibited the interaction between collagen and HSP47 by 85% and 81%, respectively, at a concentration of 1.9 µM [ 99 ].…”
Section: Changes In Hsp47 Expression Caused By Therapeutics Against P...mentioning
confidence: 99%
“…After initial screening, we manually selected 58 compounds for subsequent inhibitory activity assay according to the diversity and potential interactive mechanisms between the compounds and HSP47. Collagen molecules in a buffer of physiological pH spontaneously associated to form fibrils [17,35,36], while the turbidity gradually increased in a concentration-dependent manner and then reached a plateau phase (Figure 4a). HSP47 retarded this fibril formation process within the range of 2.0-5.2 µM (Figure 4b).…”
Section: Screening and Identification Of Hsp47 Small Molecular Inhibitorsmentioning
confidence: 99%
“…The docking grid box was defined to include the whole collagen binding region on the HSP47 surface. Apart from Com II, Hs1, and Hs55, a recently identified HSP47 inhibitor Col003 and its analogues were also selected for docking [20,36]. The docking results indicated that Com II and Col003 bind to the surface area of HSP47 involved in binding the GXR motif of collagen (colored yellow in Figure 5, subpocket1).…”
Section: Binding Modes Of Small Molecular Inhibitors On Hsp47mentioning
confidence: 99%